Meanings of Pain - van Rysewyk, Simon (Springer International Publishing : Imprint: Springer, 2016)
Although pain is widely recognized by clinicians and researchers as an experience, pain is always felt in a patient-specific way rather than experienced for what it objectively is, making perceived meaning important in the study of pain. The book contributors explain why meaning is important in the way that pain is felt and promote the integration of quantitative and qualitative methods to study meanings of pain. For the first time in a book, the study of the meanings of pain is given the attention it deserves. All pain research and medicine inevitably have to negotiate how pain is perceived, how meanings of pain can be described within the fabric of a person's life and neurophysiology, what factors mediate them, how they interact and change over time, and how the relationship between patient, researcher, and clinician might be understood in terms of meaning. Though meanings of pain are not intensively studied in contemporary pain research or thoroughly described as part of clinical assessment, no pain researcher or clinician can avoid asking questions about how pain is perceived or the types of data and scientific methods relevant in discovering the answers.